2018
DOI: 10.1038/s41467-017-02650-6
|View full text |Cite
|
Sign up to set email alerts
|

Tbx5a lineage tracing shows cardiomyocyte plasticity during zebrafish heart regeneration

Abstract: During development, mesodermal progenitors from the first heart field (FHF) form a primitive cardiac tube, to which progenitors from the second heart field (SHF) are added. The contribution of FHF and SHF progenitors to the adult zebrafish heart has not been studied to date. Here we find, using genetic tbx5a lineage tracing tools, that the ventricular myocardium in the adult zebrafish is mainly derived from tbx5a + cells, with a small contribution from tbx5a − SHF progenitors. Notably, ablation of ventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 53 publications
4
92
0
1
Order By: Relevance
“…We have shown that Cav1 is strongly expressed in the epicardium of intact hearts and that its expression is lost in cav1 cn100 hearts. Additionally, RNA-seq data show that Cav1 expression is moderate but significantly higher in cortical cardiomyocytes, but significantly higher than in trabecular cardiomyocytes (Sánchez-Iranzo et al, 2018). Caveolae are required for smooth muscle cell contractility (Gosens et al, 2011;Halayko et al, 2008) and cell contraction results in changes to membrane tension that caveolae buffer (Sinha et al, 2011).…”
Section: Impaired Heart Function and Cardiac Elasticity In Cav1 Cn100mentioning
confidence: 99%
“…We have shown that Cav1 is strongly expressed in the epicardium of intact hearts and that its expression is lost in cav1 cn100 hearts. Additionally, RNA-seq data show that Cav1 expression is moderate but significantly higher in cortical cardiomyocytes, but significantly higher than in trabecular cardiomyocytes (Sánchez-Iranzo et al, 2018). Caveolae are required for smooth muscle cell contractility (Gosens et al, 2011;Halayko et al, 2008) and cell contraction results in changes to membrane tension that caveolae buffer (Sinha et al, 2011).…”
Section: Impaired Heart Function and Cardiac Elasticity In Cav1 Cn100mentioning
confidence: 99%
“…The compaction step is specific to higher vertebrates since ventricular trabeculae are maintained in the heart of adult fishes and reptiles which retain regenerative capacity [9,30]. In adult zebrafish heart, tbx5a expression is persistent only in the trabecular myocardium and genetic fate mapping of trabecular-tbx5a+ cells shows that these cells are able to switch their fate and differentiate into cortical myocardium during both embryonic and adult heart regeneration [31]. This suggests that trabecular myocardium displays high degree of cell plasticity and/or retains proliferative ability.…”
Section: Trabecular Compactionmentioning
confidence: 99%
“…Uninjured and injured recombined adult zebrafish sox10:CreER T2 ;vmhcl:loxP-tagBFP-loxP-mCherry-NTR hearts were collected 12 days after the last 4-OHT pulse or 7 dpi respectively, and processed according to previous protocols (Sanchez-Iranzo, et al, 2018;Tessadori, et al, 2012). Atrium and bulbus arteriosus were removed to obtain only the ventricle.…”
Section: Disaggregation Of Zebrafish Hearts Cardiomyocytes Sorting Amentioning
confidence: 99%